Bank Lending, Geographical Distance, and Credit risk: An Empirical Assessment of the Church Tower Principle - Kenneth Carling; Sofia Lundberg (Sveriges Riksbank, 2002)
Does the Church Tower Principle, i.e. geographical proximity between borrowing firm and lending bank, matter in credit risk management? If so, the bank might expose itself to a greater risk by lending to distant firms and should therefore respond by rationing them harder. In this paper we incorporate the Church Tower Principle in a simple theoretical model and derive implications that are empirically testable. We use data on corporate loans granted 1994 to 2000 by a leading Swedish bank and find no evidence that the principle applies.
Keywords: D82; G21; 330; Asymmetric information; credit rationing; duration model